Biomarkers of cardiovascular disease risk in the neonatal population. (3rd April 2023) - Lianou, Alexandra; Rallis, Dimitrios; Baltogianni, Maria; Vlahos, Antonios; Milionis, Haralampos; Giapros, Vasileios
Abstract: The consistently high prevalence of cardiovascular disease (CVD) has urged the need for punctual and effective prevention. Extended research on this specific area has demonstrated the influence of fetal and neonatal periods on the risk of developing CVD in adulthood. Thus, the role of traditional and novel biological markers to the effective screening of CVD among the neonatal population is widely investigated. The objective of the present narrative review is to examine those neonatal biomarkers that may play a role in the development of CVD, to exhibit scientific data that appertain to their association with various perinatal conditions leading to CVD predisposition, and their potential role on prediction and prevention strategies. Multiple biomarkers, traditional and novel, have been mined across the studied literature. Adiposity, insulin resistance, altered lipid profile, inflammation, and endothelial dysfunction seem among the headliners of CVD. Even though various novel molecules have been studied, their clinical utility remains controversial. Therefore, it is quite important for the scientific community to find elements with strong predictive value and practical clinical use.